Single step co-extruded triple layer micro-tubular solid oxide fuel cell - Ab. Rahman, Mazlinda (2022)
Fabrication of micro-tubular solid oxide fuel cells (MT-SOFC) typically involves multiple and repetitive steps of deposition and sintering. This study aimed to develop triple-layer hollow fiber (TLHF) of MT-SOFC in a single-step fabrication, as an effort to simplify the complexity of the conventional technique. Phase inversion-based co-extrusion/co-sintering technique was employed in this study to simultaneously fabricate triple-layer anode/electrolyte/cathode hollow fiber based MT-SOFC with a desired structure. In order to overcome the challenges during the fabrication process due to the different sintering behaviors of each layer, the modification of the cathode layer had been conducted in the first stage of this study by analyzing the compatibility of different cathode materials (lanthanum strontium manganite (LSM); lanthanum strontium cobalt ferrite (LSCF)) with electrolyte material, yttria-stabilized zirconia (YSZ) at varied sintering temperature of 1250~1450 °C. Composite LSM-YSZ cathode hollow fiber had higher chemical compatibility at optimum sintering temperature of 1400 °C, in comparison to LSCF-YSZ cathode. In the second stage of the study, the effect of co-extrusion/co-sintering parameters on TLHF fabricated, namely co-sintering temperature (1300~1450 °C) and cathode extrusion rate (3~6 ml min-1), were investigated. The fabrication of TLHF via this advanced technique was optimized at 1450 °C of co-sintering temperature with 6 ml min-1 of cathode extrusion rate. Additionally, the usage of micron size YSZ at cathode site and rapid sintering rate of 10 °C min-1 are good approaches to ensure the success of the fabrication process of cathode together with anode and electrolyte; yielding 0.75 Wcm-2 of power output at 800 °C. As the co-sintering of triple-layer together might cause the densification of cathode, thus, addition of different graphite loading (2.5~15 wt.%) in cathode suspension was performed in the third stage of the study, in order to further improve the cathode structure. It was discovered that 2.5 wt.% of graphite loading enhanced the cathode structure with the generation of fine microscopic pores which were uniformly distributed throughout the cathode site. The addition of graphite, however, had reduced the size of the TLHFgr (with the presence of graphite). Thus, 8~16 ml min-1 of bore fluid flow rate was examined to improve the TLHFgr structure; and 12 ml min-1 was found to be the most suitable bore fluid flow rate in fabricating TLHFgr. Afterward, the stability analysis of TLFH and TLHFgr for 24 hrs of operation at 800 °C had been conducted in the fourth stage of the study. The result revealed that TLHF displayed a stable performance throughout the operation. Along with that, comparative analysis between MT-SOFC fabricated via singe-step preparation of phase inversion-based co-extrusion/co-sintering technique; and multiple-step preparation of phase inversion-based co-extrusion of anode/electrolyte and cathode brush-painting technique, was examined. As a result, the novel technique of single-step preparation of phase inversion-based co-extrusion/co-sintering was found to be able to offer greater performance of 1.46 W cm-2 with 1.08 V OCV at 800 °C; as well as desired TLHF MT-SOFC quality of asymmetric anode (sharp-thin finger-like void and sponge-like void), thin and dense electrolyte, and porous cathode with strong adhesion bond between the layers, compared to the conventional multiple-step preparation technique (0.09 W cm-2, 0.57 V OCV). The utilization of this new technique brought an end to cathode delamination and unsteady cathode thickness problems caused by conventional cathode deposition technique.